Application of geomorphologic factors for identifying soil loss in vulnerable regions of the Cameron Highlands - Kok K.; Sidek L.M.; Jung K.; Kim J.-C. (MDPI AG, 2023)
Catchments; Geomorphology; Soils; Watersheds; Drainage area; Power law distribution; Runoffaggregation; Soil loss; Stream power; Shear stress; drainage; geomorphology; GIS; methodology; power law distribution; river basin; runoff; shear stress; soil erosion; upland region; vulnerability; Cameroon